Seven key facts about UK living standards - Jonathan Cribb; Tom Waters (Institute for Fiscal Studies (IFS), 2024)
What has happened to average incomes, inequality, poverty, jobs and pay since 2009 and since 2019? How does the UK compare internationally?
Keywords: 330; Employment and income; Poverty; inequality and social mobility; Employment; Inequality; Inflation; Labour supply and workforce; Living standards; Pay; Poverty; Tax; Trends